2018
DOI: 10.1007/s13659-018-0178-6
|View full text |Cite
|
Sign up to set email alerts
|

The Progress of Anti-HBV Constituents from Medicinal Plants in China

Abstract: Hepatitis B virus (HBV) infection causing acute and chronic hepatitis is a serious problem worldwide, whereas the current treatment methods are unsatisfactory. Traditional Chinese herbs that have long been used for medicinal purposes are fascinating sources for novel anti-HBV candidates. This paper summarizes the progress of anti-HBV constituents from diverse medicinal plants in China to provide information for searching new anti-HBV drugs from natural sources.Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The root bark of Illicium henryi Diels (Illiciaceae), commonly known as Chinese anise tree or hardwood crab, has been used for alleviating pain and swelling, removing phlegm, promoting blood circulation, and dispelling pathogenic wind, cold and dampness in traditional Chinese medicine [18,19]. Modern pharmacological studies have shown that this drug possesses anti-inflammatory, antioxidant, anti-hepatitis B virus, and anti-HIV activities [20,21]. The root bark of I. henryi has been reported to contain flavonoids, prenylated C6–C3 compounds, sesquiterpene lactones, triterpenoids, lignans, and neolignans [18,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The root bark of Illicium henryi Diels (Illiciaceae), commonly known as Chinese anise tree or hardwood crab, has been used for alleviating pain and swelling, removing phlegm, promoting blood circulation, and dispelling pathogenic wind, cold and dampness in traditional Chinese medicine [18,19]. Modern pharmacological studies have shown that this drug possesses anti-inflammatory, antioxidant, anti-hepatitis B virus, and anti-HIV activities [20,21]. The root bark of I. henryi has been reported to contain flavonoids, prenylated C6–C3 compounds, sesquiterpene lactones, triterpenoids, lignans, and neolignans [18,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…17 It has also been postulated that some medicinal plants used in Traditional Chinese Medicine exhibit anti-HBV activity. 13 Several plants native to the Arabian Peninsula: Guiera senegalensis, Pulicia crispa, Coccinea grandis, Fumaria parviflora, Capparis decidua, Corallocarpus epigeus, Indigofera caerulea, Abutilon figarianum and Acacia oerfota have also been found to possess anti-HBV activity by inhibiting hepatitis B surface antigen (HBsAg) and hepatitis B e antigen (HBeAg) in the cell culture supernatant. 18 Our previous study also reported that Cananga odorata exhibited strong inhibition of the hepatitis B virus in Hep38.7-Tet and HepG2-NTCP cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that piperine and guineesine, isolated compounds of Piper longum, exhibit inhibitory activity suppressing the secretion of HBsAg and HBeAg with IC 50 values of 0.15 and 0.05 mM for HBsAg, and 0.14 and 0.05 mM for HBeAg, respectively. 13 Our previous study was reported Cananga odorata possessed a strong anti-HBV activity both in HepG2-NTCP and Hep38.7-Tet cells which indicated the action of extract in the entry and post entry steps (replication) of HBV life cycle. 14 In this study, we screened 31 samples of Indonesian medicinal plants for anti-HBV activity by two invitro assays to assess the effect on the viral entry and replication.…”
Section: Introductionmentioning
confidence: 91%
“…The plant possesses several bioactive compounds, including xanthones, flavonoids, triterpenoids, alkaloids, which have been shown to be effective as anti-oxidant, antibacterial, antifungal, and antiviral. 98,101,102 The bioactive compounds that inhibit 3CLpro, making them valuable against CoVs, are Kouitchenside and Oleanolic acid. 24 Other species in Swertia genus with potential anti-SARS CoV activity include Swertia binchuanensis, Swertia macrosperma, Swertia maculate, Swertia mussotii.…”
Section: Camellia Sinensismentioning
confidence: 99%